(untitled) (Scientific journal of the Fergana State University, 2024)
The article shows that soils are exposed to anthropogenic and man-made factors, and for several years heavy metals, nitrites and fluorine contained in mineral fertilizers accumulate in the soil under the main arable layer. But it was noted that the industry lacks modern innovative and information and communication technologies that allow assessing the real sanitary and environmental condition of the country. More than a hundred substances and chemical compounds that enter the soil as a result of irrigation over the years eventually enter the soil and decompose it. This means that more than a hundred substances and chemical compounds that enter the soil as a result of irrigation over many years eventually enter the soil and decompose it.